FORMATION OF STUDENTS' RESEARCH SKILLS IN THE SYSTEM OF INTEGRATED EDUCATION BASED ON A COMPETENCE-BASED APPROACH - Axmadova Feruza Zarifovna; Raxmatullayeva Dildora Fozilovna (American Journals, 2023)
The article highlights the relevance of integrated education, research activities of students in English lessons, the essence of competence, topical issues of the formation of research skills of students.
Keywords: Research skills, competence approach, competence, integration, integrative approach, interactive forms of learning, integrative lesson, integrative day.